MATHEMATICAL COMMUNICATION OF STUDENTS IN COMPLETING SPLTV IN TERMS OF MATHEMATICAL ABILITY - Revlin Alifia Kusuma; Janet Trineke Manoy (Program Studi S1 Matematika UNESA, 2022)
Mathematics learning will achieve satisfactory results if it can meet all standards in the learning process, including mathematical communication skills. Mathematical communication is an ability to understand problems by modeling them into mathematical symbols and explaining mathematical ideas in writing or orally. This research with descriptive qualitative method aims to describe the mathematical communication skills of students with high and moderate mathematical abilities in class X in solving SPLTV questions. The data collection technique used a written test in the form of SPLTV material story questions and interviews as supporting data. The results showed that students who had high mathematical ability fulfilled all indicators of mathematical communication correctly, while students who had moderate mathematical ability met the indicators of mathematical communication in understanding the core of the problem and mentioning what is known and asked in the question. It is hoped that the teacher will be able to improve students' mathematical communication skills by applying story questions whose answers have mathematical communication indicators so that students are increasingly able to express mathematical ideas both in writing and verbally and are able to fulfill all indicators of mathematical communication.